Intranasal Immunization with Pressure Inactivated Avian Influenza Elicits Cellular and Humoral Responses in Mice. - Shana P C Barroso (PLoS ONE, 2015)
Influenza viruses pose a serious global health threat, particularly in light of newly emerging strains, such as the avian influenza H5N1 and H7N9 viruses. Vaccination remains the primary method for preventing acquiring influenza or for avoiding developing serious complications related to the disease. Vaccinations based on inactivated split virus vaccines or on chemically inactivated whole virus have some important drawbacks, including changes in the immunogenic properties of the virus. To induce a greater mucosal immune response, intranasally administered vaccines are highly desired as they not only prevent disease but can also block the infection at its primary site. To avoid these drawbacks, hydrostatic pressure has been used as a potential method for viral inactivation and vaccine production. In this study, we show that hydrostatic pressure inactivates the avian influenza A H3N8 virus, while still maintaining hemagglutinin and neuraminidase functionalities. Challenged vaccinated animals showed no disease signs (ruffled fur, lethargy, weight loss, and huddling). Similarly, these animals showed less Evans Blue dye leakage and lower cell counts in their bronchoalveolar lavage fluid compared with the challenged non-vaccinated group. We found that the whole inactivated particles were capable of generating a neutralizing antibody response in serum, and IgA was also found in nasal mucosa and feces. After the vaccination and challenge we observed Th1/Th2 cytokine secretion with a prevalence of IFN-γ. Our data indicate that the animals present a satisfactory immune response after vaccination and are protected against infection. Our results may pave the way for the development of a novel pressure-based vaccine against influenza virus.